Attitudes of the autism community to early autism research. (January 2017) - Fletcher-Watson, Sue; Apicella, Fabio; Auyeung, Bonnie; Beranova, Stepanka; Bonnet-Brilhault, Frederique; Canal-Bedia, Ricardo; Charman, Tony; Chericoni, Natasha; Conceição, Inês C; Davies, Kim; Farroni, Teresa; Gomot, Marie; et al.
Investigation into the earliest signs of autism in infants has become a significant sub-field of autism research. This work invokes specific ethical concerns such as use of 'at-risk' language, communicating study findings to parents and the future perspective of enrolled infants when they reach adulthood. This study aimed to ground this research field in an understanding of the perspectives of members of the autism community. Following focus groups to identify topics, an online survey was distributed to autistic adults, parents of children with autism and practitioners in health and education settings across 11 European countries. Survey respondents (n = 2317) were positively disposed towards early autism research, and there was significant overlap in their priorities for the field and preferred language to describe infant research participants. However, there were also differences including overall less favourable endorsement of early autism research by autistic adults relative to other groups and a dislike of the phrase 'at-risk' to describe infant participants, in all groups except healthcare practitioners. The findings overall indicate that the autism community in Europe is supportive of early autism research. Researchers should endeavour to maintain this by continuing to take community perspectives into account.